(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2019)
Urban and suburban transport is a transport system that combines various types of transport, transporting people and goods in the city and the nearest suburban area, as well as performing work on the improvement of the city. The urban transport system is part of a diversified urban economy and includes: vehicles (rolling stock); track devices (rail tracks, tunnels, overpasses, bridges, overpasses, stations, parking lots); marinas and boat stations; power supply devices (traction power substations, cable and contact networks, gas stations); repair shops and factories; depot, garages, service stations; car rental offices; linear communication devices, alarms, locks, traffic control. The city’s transport system also includes a bicycle, for which in civilized countries a special bicycle path on the sidewalks is allocated. The urban passenger transport is faced with the task of delivering passengers to their destination with maximum comfort at the minimum cost of time, labour and resources. The territorial development of cities at all times of their history was determined primarily by the speed characteristics of mass intracity movements. Therefore, the famous architect, creator of modern cities Le Corbusier noted that no city can grow faster than its transport. In this article, we introduce a new approach to modelling by using network theory and calculating topological properties of network, which have practical applications in transportation and urban traffic network. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.